Training rural development managers - Misajon, Mervyn J. (1993)
Poor program administration and poor condition of services are two major reasons for the failures of rural development programs. These shortcomings point to the need for an improved administrative capability through trained manpower adept in planning, managing, and operating rural development efforts particularly at the field level. Although training is one approach for improving administrative capability, proper identification of training needs is vital to come up with an appropriate training design suited to the peculiarities of the areas and the traditional as well as actual tasks performed by rural development managers. Only by identifying these needs can training programs imbibe the knowledge, skills, and values required by today's and tomorrow's rural development managers.
Keywords: Civil service personnel management; Training of civil service; Rural development